The Use of Vancomycin Powder for Surgical Prophylaxis Following Craniotomy. Issue 5 (May 2017) - Ravikumar, Vinod; Ho, Allen L.; Pendhakar, Arjun V.; Sussman, Eric S.; Kwong‐hon Chow, Kevin; Li, Gordon
Abstract : BACKGROUND: : Intrawound vancomycin powder has been studied extensively in spinal fusion surgeries and been found to reduce rates of surgical site infections (SSIs) significantly. Despite its success in spinal surgeries, topical vancomycin has not been extensively studied with respect to cranial neurosurgery. OBJECTIVE: : To evaluate the efficacy of intrawound topical vancomycin for prevention of SSIs following open craniotomies. METHODS: : We retrospectively analyzed a large series of 350 patients from 2011 to 2015 in a pre/postintervention study of use of topical vancomycin to reduce postoperative craniotomy infection rates. We had a preintervention control group of 225 patients and a postintervention group of 125 patients that received intrawound topical vancomycin. RESULTS: : Our preintervention incidence of SSI was 2.2% and this was significantly reduced to 0% following introduction of topical vancomycin ( P < .5). An ad hoc cost analysis suggested a cost savings of 59 965 with the use of topical vancomycin for craniotomies. CONCLUSION: : Our study found a significant reduction in SSI rates after introduction of topical vancomycin. Thus, this simple intervention should be considered in all open craniotomy patients as both infection prophylaxis and a potential cost saving intervention.